Orphan breakwaters – what protection is given when they collapse?. Issue 4 (11th January 2019) - Allsop, Nigel William Henry; Pearson, Adrian N.; Bruce, Tom
Abstract : Many old coastal harbours in the UK are protected by blockwork breakwaters, but the original streams of income for maintaining or refurbishing these structures have largely diminished. Their breakwaters may, however, still protect harbour-side properties against wave overtopping, and thus flooding. This paper presents results from an exploratory study to identify how the blockwork breakwaters common in many smaller UK coastal harbours may collapse due to storm action and how much wave protection is given by collapsed breakwaters.